2015
DOI: 10.1007/s10683-015-9458-8
|View full text |Cite
|
Sign up to set email alerts
|

Pricing competition: a new laboratory measure of gender differences in the willingness to compete

Abstract: Experiments have demonstrated that men are more willing to compete than women. We develop a new instrument to "price" willingness to compete. We find that men value a $2.00 winner-take-all payment significantly more (about $0.28 more) than women; and that women require a premium (about 40 percent) to compete. Our new instrument is more sensitive than the traditional binary-choice instrument, and thus, enables us to identify relationships that are not identifiable using the traditional binary-choice instrument.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 19 publications
(14 reference statements)
4
34
0
Order By: Relevance
“…All three studies find that the magnitude of men's willingness‐to‐compete is greater than women's and that the new measures are more informative than the binary‐choice measure. The new willingness‐to‐compete measure validated in Ifcher and Zarghamee (forthcoming) is utilized herein to examine a disparate research question: whether performing is necessary and sufficient to generate gender‐variant preferences for competition. As such, the study of Ifcher and Zarghamee (forthcoming) does not consider the data generated from the task without agency (described in Section III.D) and restricts the sample to the 108 (of 208) subjects that completed the summation task first.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…All three studies find that the magnitude of men's willingness‐to‐compete is greater than women's and that the new measures are more informative than the binary‐choice measure. The new willingness‐to‐compete measure validated in Ifcher and Zarghamee (forthcoming) is utilized herein to examine a disparate research question: whether performing is necessary and sufficient to generate gender‐variant preferences for competition. As such, the study of Ifcher and Zarghamee (forthcoming) does not consider the data generated from the task without agency (described in Section III.D) and restricts the sample to the 108 (of 208) subjects that completed the summation task first.…”
Section: Experimental Designmentioning
confidence: 99%
“…In Task 4, subjects were offered the payment scheme from Ifcher and Zarghamee (forthcoming) that measures the willingness to compete along a continuum. Specifically, subjects were offered a series of choices between PR payments (ranging from 0% to 100% of the WTA payment) and the WTA payment.…”
Section: Experimental Designmentioning
confidence: 99%
“…There are, however, some exceptions. Females are more willing to compete against other women (Gupta, Poulsen, & Villeval, 2013) and at tasks at which they feel they excel (Ifcher & Zarghamee, 2015). Overall, however, the net result is that fewer women enter male-dominated fields.…”
Section: 1 Introductionmentioning
confidence: 99%
“…Ifcher and Zarghamee, (), use an MPL and reported that out of 151 subjects, 23 had irrational reactions (shifted between the tournament and the piece‐rate more than once). It is true that by “forcing” rationality, we might miss some of the natural errors humans make, which can yield some interesting information for the researcher.…”
mentioning
confidence: 99%
“…Ifcher and Zarghamee, () report a Spearman rank correlation = 0.61 ( p = 0.00) and argue that this is “suggesting that both instruments are measuring a similar parameter.”…”
mentioning
confidence: 99%